PENGARUH PENERAPAN FULL DAY SCHOOL TERHADAP MOTIVASI BELAJAR SISWA DI UPT SMA NEGERI 11 WAJO KECAMATAN TAKKALALLA KABUPATEN WAJO - Sitti Aminah; Erviana Abdullah; Sumarni; Adi Kurnia; Feryaldi; Sri Nur Rahmi Rosmiati; Dzul Fahmi Hamzah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article explores the impact of implementing the Full Day School system on students' learning motivation within educational institutions. The study is driven by the need for innovation in learning methods to enhance the overall quality of education, particularly in fostering student motivation. Since its adoption in 2018 at UPT SMA Negeri 11 Wajo, the Full Day School program has continued to generate mixed reactions among students, teachers, and parents. Some students report increased motivation, while others express feelings of fatigue and boredom. Using a quantitative research approach, the study reveals that the Full Day School model significantly affects students' learning motivation at UPT SMA Negeri 11 Wajo, accounting for 62.3% of the influence, with the remaining 37.7% attributed to other factors.